The effectiveness of ReAttach Therapy for Fibromyalgia Patients analyzed by the Symptom Amplification Model of Neurolog: A study protocol. (ReAttach Affect Coach Journal, 2025)
Fibromyalgia, a chronic widespread musculoskeletal pain condition affecting approximately 2 to 3 percent of adults [1,2], often co-occurs with symptoms like fatigue, cognitive issues, and psychological problems such as anxiety and depression. The ongoing need to assess psychosocial interventions remains critical, given the multifactorial nature of fibromyalgia despite emerging research on non-invasive neuromodulation, virtual reality, and psychedelic therapies. ReAttach, a tailored, multimodal transdiagnostic intervention, might meet the need for a personalized approach in fibromyalgia [3]. This study protocol is part of a series of studies investigating the efficacy of ReAttach in biopsychosocial conditions [4,5,6,7]. The research will utilize the Emotions Symptom Regulation Model and Symptom Amplification Model, created by Painter (2025), which provide innovative tools to detect and analyze changes in symptom networks [4]. This approach aims to deepen understanding of fibromyalgia's complex mechanisms and the potential impact of ReAttach.
Keywords: Fibromyalgia; ReAttach; OT; Symptom Amplification Model; Psychobiosocial Conditions